Rola systemu motywacyjnego w realizacji celów przedsiębiorstwa i kształtowaniu przewagi konkurencyjnej przedsiębiorstwa na rynku na przykładzie firmy TRANS SPED - Grzyb, Beata (My University, 2012)
Dobrze zbudowany system motywacyjny przyczynia się do zwiększenia przewagi konkurencyjnej poprzez pozyskanie i utrzymanie kompetentnych pracowników. Głównym celem niniejszej pracy było określenie wpływu wewnątrzzakładowego systemu motywacyjnego na budowaną przewagę konkurencyjną firmy Tran Sped i realizowane przez nią cele rozwojowe. W pracy tej przyjęto następujące hipotezy badawcze: Pomiędzy strategią firmy a systemem motywacyjnym występuje efekt sprzężenia zwrotnego. Strategia firmy kształtuje system motywacyjny, a z drugiej strony system motywacyjny wspiera strategię i jej realizację. Determinantem powodzenia realizacji strategii przedsiębiorstwa jest system motywacyjny, który w istotny sposób wspiera proces budowania przewagi konkurencyjnej na rynku i realizację celów strategicznych. Bodźce motywacyjne materialne skuteczniej wspierają proces realizacji celów firmy od bodźców niematerialnych. Część teoretyczna niniejszej pracy przedstawia teoretyczne aspekty zarządzania zasobami ludzkimi. Część badawcza to analiza systemu motywacyjnego w realizacji celów oraz kształtowania przewagi konkurencyjnej firmy. Badania przeprowadzono na grupie pracowników umysłowych jak i fizycznych. W wyniku badań, wyciągnieto wnioski, iż większość pracowników pozytywnie oceniła działania systemu motywacyjnego, który w istotny sposób wspiera proces budowania przewagi konkurencyjnej na rynku i realizację celów rozwojowych związanych z wysoką jakością obsługi klienta.

A well-designed motivation system contributes to a company's increased competitive advantage by gaining and maintaining competent employees. The main objective of this work is to define the influence of an in-house motivation system on building Tran Sped company's competitive advantage and on the company's realized development objectives. The following research hypothesis has been chosen for this thesis: There is a back and forth feedback effect between the strategy and the motivation system of the company. The company's strategy forms a motivation system, and the motivation system, in turn, supports strategy and its realization. The determinant of a company's realized success is its motivation system which significantly supports the process of building competitive advantage in the market, as well as the achievement of strategic objectives. Material incentives effectively promote the objectives of the company from intangible incentives. The theoretical part of this work presents the theoretical aspects of human resources management. The research part is an analysis of the actual motivation system in accomplishing objectives and forming competitive advantage for the company. The research completed at Trans Sped company was done on a group of white-collar workers, as well as on a group of manual workers. Based on the results of the carried out research analysis, the conclusion reached was that the vast majority of the employees hold a positive opinion about the motivation system which significantly supports the process of building competitive advantage in the market and the realization of development objectives connected to the high quality of customer service. Between the company’s strategy and the motivation system there is a feedback effect which confirms that the motivation system used in Trans Sped company contributes to its development and improves its functioning as a whole.
The role of motivational system in achieving the objectives of the company and developing its competitive advantage in the market on the example of TRANS SPED
Keywords: zarządzanie zasobami ludzkimi; system motywacyjny; TRANS SPED; motywacja; czynniki motywacyjne; strategia; przewaga konkurencyjna; cele przedsiębiorstwa; human resources management; motivation system; motivation; incentive factors; strategy; competitive advantage; objectives of the company